Excessive reassurance-seeking and anxiety among Chinese new urban older adults: the role of attention to negative information and resilience - Sun, Yang; Wrzus, Cornelia; Lv, Shaobo (BMC geriatrics, 2025)
Policy-driven relocation of older adults from rural to urban areas in China is a significant stressor that often exacerbates anxiety. The mechanisms through which excessive reassurance seeking (ERS) heightens anxiety in this population remain poorly understood.
Gesehen am 16.01.2026